Regular and uniform-shaped BaTiO3 microplates prepared using a modified precursor. Issue 2 (1st February 2019) - Hao, Mengmeng; Fan, Guifen; Lou, Yihui; Wen, Yue; Deng, Haoyuan; Wang, Fei; Lv, Wenzhong; Yuchi, Ming; Ding, Mingyue
Abstract: Regular and uniform-shaped BaTiO3 microplates have been prepared using a modified topochemical microcrystal conversion (TMC) method. The BaTiO3 platelets are approximately 10 µm × 10 µm × 0.5 µm in rectangular shape. The precursor has a significant effect on the shape of BaTiO3 microplates. In aurivillius precursors, the perovskite blocks sandwiched by [Bi2 O2 ] slabs are misaligned alongc axis, which will cause exfoliation during TMC. When using Bi4 Ti3 O12 or polycrystalline BaBi4 Ti4 O15 as a precursor, exfoliation occurs, which leads to small BaTiO3 particles. However, single-crystalline BaBi4 Ti4 O15 precursor exhibits continuity within the platelets. The continuity of BaBi4 Ti4 O15 inhibits the exfoliation of BaTiO3 microplates. The well-shaped BaTiO3 microplates derived from the single-crystalline BaBi4 Ti4 O15 precursor are proved to be suitable for textured ceramics.